EVALUATION OF THE IMPLEMENTATION OF LOVE-BASED CURRICULUM IN ISLAMIC JUNIOR HIGH SCHOOLS USING THE STUFFLEBEAM CIPP MODEL - Mifkhudin; Darodjat; Sriyanto; Ahmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The Love-Based Curriculum (KBC) is a strategic policy of the Ministry of Religious Affairs of the Republic of Indonesia through the Decree of the Director General of Islamic Education Number 6077 of 2025 which instills the values of Panca Cinta in learning in madrasas. Although it has been implemented nationally, no research has evaluated the quality of its implementation measurably using a program evaluation model at the Madrasah Tsanawiyah level. This study aims to evaluate the implementation of KBC at MTs Nurul Islam Bayung Lencir using the CIPP (Context, Input, Process, Product) model from Stufflebeam. The study used a mixed methods approach with a sequential explanatory design involving 171 respondents, consisting of one madrasah principal, 18 teachers, and 152 students. Data were collected through questionnaires, interviews, observations, and documentation studies, then analyzed and triangulated. The results showed that the overall implementation of KBC was in the Good category (83.49%). The Context component received the highest score (87.81%, Very Good), indicating that the program is aligned with the needs of students and madrasah policies; The Process component also scored Very Good (81.69%) through habituation and exemplary behavior. Meanwhile, the Input component received the lowest score (80.34%, Good) due to weak documentation and supporting administration, and the Product component (84.12%, Good) showed a positive impact on student character even though the reporting system was still manual. This study provides a measurable evaluation framework based on CIPP for the implementation of KBC in madrasas as well as data-based improvement recommendations for madrasa managers and Islamic education policy makers.